Performance of Garden Pea Varieties as Intercrop with Maize in the Coastal Area of Bangladesh - SHAHADAT, MUSTAFA KAMAL; RASHID, MD HARUNOR; ALI, MD AKKAS (Journal of the Indian Society of Coastal Agricultural Research, 2019)
An experiment was conducted in the coastal saline area of Khulna, Bangladesh during rabi seasons of 2014-15, 2015-16 and 2016-17 to find out the performance of garden pea varieties as intercrops with hybrid maize. Three intercropping treatment combinations were investigated along with two sole crops. Treatment combinations were T1: Two rows of garden pea variety (BARI Motorshuti-1) in between two rows of maize, T2: Two rows of garden pea variety (BARI Motorshuti-3) in between two rows of maize, T3: Two rows of local garden pea in between two rows of maize, T4: Sole maize (BARI Hybrid Maize-9) (60 cm X 20 cm spacing) and T5 = Sole garden pea with local variety (25 cm row spacing). There was no significant variation among the years in terms of growth and yield component characters of maize and garden pea varieties. Pooled data over the three years showed that the growth and yield component characters of maize varied significantly due to incorporation of different garden pea varieties, whereas significant variation was observed among the garden pea varieties in terms of plant height, thousand pod weight and pod yield. Incorporation of garden pea varieties as intercrop with maize increased maize equivalent yield (MEY). Maximum MEY was obtained from maize + BARI Motorshuti-3 (24.90 t ha-1). Moreover, in T2, percent yield reduction in maize (-8.66%) and garden pea (-17.04%) was lowest than other intercrop treatments consisting of other garden pea varieties. The values of all the competition functions and intercrop efficiency index showed superiority of maize + BARI Motorshuti-3 (T2) intercropping than other garden pea varieties. Treatment T2 also showed higher values of land equivalent ratio (1.74), gross return (Tk. 373500 ha-1), gross margin (Tk. 238000 ha-1) and BCR (2.76) as compared to other treatments.